Building Information Modelling (BIM) Adoption by Quantity Surveyors: A Preliminary Survey from Malaysia. Issue 5 (May 2019) - Ismail, Noor Akmal Adillah; Adnan, Hamimah; Bakhary, Nor Azmi
Abstract: Inefficiencies and ineffectiveness of delivering construction projects have negatively impacted the construction industry for decades. However, the emergence of BIM technology has influenced the construction process with its many benefits towards project success. Among the benefits offered by BIM are reduced project time and cost; and enhanced team collaboration and communication through the improvement of project quality and its performance. Consequently, BIM applications are claimed to provide more reliable working practice for Quantity Surveyors especially in establishing their cost estimates. Despite its well-known advantages that drive BIM employment worldwide, its usage in Malaysia is still at infancy level, with the lack of implementation by the Quantity Surveyors. Thus, this paper aims to explore BIM usage amongst Quantity Surveyors in Malaysia. A preliminary survey was undertaken to capture their views on BIM awareness, the application of BIM software, BIM usage by project stages, prospects of BIM and its importance. The findings from the survey show that BIM implementation amongst the professionals was still low. The application of BIM tools was used mostly for cost estimating and preparing Bills of Quantities (BQ) for tender documentation purpose only. Although BIM was mostly rated as important, most of the respondents were only aware of BIM but were not using it in their practice. However, they showed their interest in knowing more on how BIM would benefit their practice. The significance of this preliminary study is in terms of getting input on BIM adoption level amongst the construction players focusing on the quantity surveying field, which could be used as a reference point and benchmark towards BIM development in Malaysia.